Políticas públicas para integração de tecnologias educacionais na formação inicial de professores - Toebe, Iris Cristina Datsch (2016)
The technological transformations observed in society in general have also occupied a space of study in the field of education. Educational technologies present possible changes and improvements regarding the initial teacher training process, since they allow for curricular and methodological innovation, as well as providing the democratization of education through distance education. In this sense, this research had as objective to analyze orientations of the public policies for the integration of the educational technologies in the school practices of the courses of initial formation of professors (licenciatura in Pedagogy and Special Education) of the Center of Education (CE) of the Federal University of Santa Maria ( UFSM). In terms of methodology, we developed action research through the assumptions of the spiral cycle of Kemmis and Mctaggart (1988) through (re) planning, action, observation and reflection reinforcing its foundations in Paulo Freire's dialogical-problematizing education and Discursive Textual Analysis Proposed by Moraes and Galiazzi (2011). As instruments for data production were prioritized: questionnaires with open and closed questions; Analysis of educational public policies for teacher education; Analysis of the pedagogical projects of the courses; Observations and follow-up of the planning and development of courses for undergraduate courses. After the analysis, based on the triangulation of the data, it was possible to perceive that the guidelines of the public policies need to be better systematized in the pedagogical projects of course. Thus, the integration of educational technologies into the curricular activities of teacher training courses requires action both in the educational management and in the teaching performance. It is concluded that the development of technological-pedagogical fluency in higher education and basic education is fundamental to expand didactic-methodological innovation based on interaction, dialogue-problematizing and collaboration mediated by networked educational technologies.